Modelling and Simulation of a Stand-Alone Solar System with A Capacity of 380V, 39A Based on Ferrite Transformers and Half Cut Cell PV Modules - Shukir, Samhar Saeed; Murmoos, Jalil Jefred; Hussein, Amer Abdullah (Journal of Advanced Industrial Technology and Application, 2023)
The easy installation of the solar energy system, no need for fuel, low maintenance and operation requirements, makes it the preferred choice to solve the problem of power outage especially in the day of the summer season. The downside of the solar energy systems is decreasing the generated energy with the rising in temperatures, perfect and simple design of the solar energy system makes it durable over a wide range of temperature increases. This research presents the design of 3-ph (380V, 39A) stand –alone solar system at latitude 32.5 with a high quality voltage and current even when the temperature reaches to maximum levels. The power system of the project contains: 60 PV modules of a half cut cell to reduce the losses in connection lines, and two Mn-Zn toroid core ferrite transformers to transition the solar energy to the inverter with appropriate voltage efficiently. Control system is implemented based on PI controllers for switching function at a certain values of a modulation index parameter (m). The system is modeled and simulated in MATLAM/Simulink, simulation results demonstrate that the rated voltage and current have been obtained with minimum values of Total Harmonics Distortion (THD) and modulation index parameter less than 1.